The tropical version of El Gamal Encryption - Muanalifah, Any; Isnawati, Ayus Riana; Artes Jr., Rosalio; Nurwan, Nurwan (Journal of Natural Sciences and Mathematics Research, 2023)
In this paper, we consider the new version of tropical cryptography protocol, i.e the tropical version of El Gamal encryption.  We follow the ideas and modify the clasical El Gamal encryption using tropical matrices and matrix power in tropical algebra. Then we also provide a toy example for the reader’s understanding.